Analisis Kesalahan Mahasiswa Dalam PenyelesaianMasalah Diferensial - Bela Wulandari, Noviana, Masduki, M.Si (2016)
The aim of this study includes 1) identifying error made by students in completing derivative of implicit function. 2) identifying error made by students in completing the derivative function parameters. This type of research is quantitative descriptive, using the subject as many as 49 students. Data collection techniques using the test methods and documentation. Data analysis technique is done by data reduction, data presentation and conclusion. The results of this study indicate that 1) Errors in completing the derivative function implicitly includes: misconception that do not alter the function y to f (x, y) resulting in an error instance, wrong in doing drop against the variable y, and misunderstood concepts derivative of implicit functions that impact on the process of problem solving. Error principle that mistakes in interpreting and using the implicit function derivative formula. Operating errors are errors in write operation marks the final result. Error carelessness that is an error in the count because the student did not lower the carelessness with the variable y. 2) An error in completing the derivative function parameters include: misconception that mistake in understanding the concept of derivative and derivative function parameter application of the formula in solving problems. Errors are errors in interpreting the principle of mathematical formulas and wrote the formula derived. Error operation is a typing error in the operation of the formula derived .. Error carelessness that inconsistency in the writing operation marks and errors in the calculation.